Does farmer participatory research matter for improved soil fertility technology development and dissemination in Southern Africa? - Rusike, Joseph; Twomlow, Stephen; Freeman, H.; Heinrich, G. (2006)
Crop management research is increasingly involving farmers in evaluating new technologies, identifying adoption constraints and opportunities for improving farm performance to produce more sustainable impact. ICRISAT and its partners worked with farmers in Malawi and Zimbabwe during the 1999/2000 and 2000/2001 seasons to evaluate a range of ‘best bet’ soil fertility and water management technologies and evaluate the impact of farmer participatory research. Although there was some variation in methods implemented at different sites, the study found that there is a basis for a comparison of methods. Community entry and participatory approaches that engage farmers in decision making throughout the research-development-diffusion-innovation process have higher setup costs compared to traditional ‘top-down’ approaches. But they improve efficiency, both in technology development and in building farmers' capacity for experimentation and collective learning. This results in the development of more relevant technologies, joint learning among farmers, researchers and extensionists and better impact. To make farmer participatory research projects more sustainable and introduce them on a wide scale, the study recommends that public and NGO investments be targeted to building district and village-level innovation clusters.